The Effect of Service Quality on Customer Satisfaction in Ranking Learning Guidance Services Deli Serdang Branch - Zendrato, Ferawati; Napitu, Marolop Parlindungan; Sembiring, Veramika br (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The research aims to identify and analyze the influence of service quality consisting of physical tangible, reliability, responsiveness, assurance, and empathy on service quality to customer satisfaction on User of Ranking Deli Serdang Tutoring Service. The population in this research is high school students who use Ranking Deli Serdang Tutoring Service totaling 218 customers. The sample in this observation was 70 respondents. The collecting of primary data is done by using questionare which is means measured by Likert Scale. Secondary data was obtained from books related to the observation. Hypothesis testing is done by using multiple linear regression analysis. The results of the analysis indicate that service quality that includes tangible, reliability, responsiveness, assurance and empathy is positive and significant impact to customer satisfaction on User of Ranking Deli Serdang Tutoring Service. The result of partial significance test shows that physical evidence, responsiveness, assurance, and empathy have positive and significant effect to customer satisfaction, while reliability has positive and insignificant effect to customer satisfaction on User of Ranking Deli Serdang Tutoring Service. And the F test results are Ftable = 2.36, where Fcount > Ftable (63.263 > 2.36) which means that simultaneously there is a positive and significant influence of the independent variables namely physical evidence, reliability, responsiveness, assurance, and empathy on the dependent variable on student satisfaction in Deli Serdang Ranking Tutoring.